A public health initiative for reducing access to pesticides as a means to committing suicide: Findings from a qualitative study. (August 2014) - Mohanraj, Rani; Kumar, Shuba; Manikandan, Sarojini; Kannaiyan, Veerapandian; Vijayakumar, Lakshmi
Abstract Widespread use of pesticides among farmers in rural India, provides an easy means for suicide. A public health initiative involving storage of pesticides in a central storage facility could be a possible strategy for reducing mortality and morbidity related to pesticide poisoning. This qualitative study explored community perceptions towards a central pesticide storage facility in villages in rural South India. Sixteen focus group discussions held with consenting adults from intervention and control villages were followed by eight more a year after initiation of the storage facility. Analysis revealed four themes, namely, reasons for committing suicide and methods used, exposure to pesticides and first-aid practices, storage and disposal of pesticides, and perceptions towards the storage facility. The facility was appreciated as a means of preventing suicides and for providing a safe haven for pesticide storage. The participatory process that guided its design, construction and location ensured its acceptability. Use of qualitative methods helped provide deep insights into the phenomenon of pesticide suicide and aided the understanding of community perceptions towards the storage facility. The study suggests that communal storage of pesticides could be an important step towards reducing pesticide suicides in rural areas.